DAYA TERIMA DAN KADAR ALKOHOL PADA TAPE KULIT SINGKONG BERDASARKAN VARIASI JUMLAH RAGI - agus marjoko; wikanastri hersoelistyorini (Universitas Muhammadiyah Semarang, 2011)
Tapae is Indonesian traditional food made of materials that contain many carbohydrates such as cassava, rice and sorghum. Tapae can also be made from cassava peel, commonly called cassava peel tape. The general objective of this study was to determine the effect of variations in the addition of yeast to acceptance and alcohol content of cassava peel tapae. Organoleptic properties including flavor, texture, aroma and color. Increasing the number of yeast 0.5%, 1%, 1.5% and 2%. This type of research the effect of variations in the addition of yeast to consumer acceptance and ethanol content is experimental research. The results of organoleptic test is the most preferred by the addition of yeast 1,% seen from the parameter tape distinctive aroma smell, sweet taste is a bit sour, soft and soft texture. The highest alcohol content on the addition of the yeast 2% with an average 3.4%, for the lowest is the addition of yeast variation of 0.5%, with an average of 0.7%.